Acetic acid modified aluminum oxide coated titanium dioxide adsorbent as well as preparation method and application thereof
The acetic acid modified alumina coated titanium dioxide adsorbent effectively addresses the challenge of removing trace PCl3 in solar-grade polysilicon production by enhancing adsorption capacity and stability, achieving efficient and cost-effective PCl3 removal with recyclability.
Patent Information
- Application Number
- CN202411280067.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
Existing alumina adsorbents have weak adsorption capacity and slow adsorption rates for removing phosphorus trichloride (PCl3) at ppb levels, which is a critical impurity in the production of solar-grade polysilicon, necessitating the development of an adsorbent that can efficiently remove trace amounts of PCl3.
An acetic acid modified alumina coated titanium dioxide adsorbent is prepared using a hydrothermal co-precipitation method with titanium sulfate and aluminum nitrate, followed by acetic acid impregnation, resulting in a flower ball-shaped adsorbent with mesoporous and macroporous structures, enhancing its electrophilic properties and specific surface area for effective PCl3 removal.
The adsorbent achieves PCl3 removal to less than 10 ppb levels, is reusable after regeneration, and has a high specific surface area, pore volume, and improved adsorption capacity, outperforming commercial resins and reducing material consumption and costs.
Smart Images

Figure CN119140064A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adsorbent preparation, and in particular to an acetic acid modified alumina coated titanium dioxide adsorbent and a preparation method and application thereof. Background Art
[0002] With the rapid development of global industrialization, problems such as energy shortage, greenhouse effect and environmental pollution are becoming increasingly serious. In order to effectively deal with the above problems, the development and utilization of clean energy is particularly important. Among many clean energy sources, solar energy technology is relatively mature and has been widely used in many fields. According to statistics, more than 95% of solar energy technologies rely on polysilicon products. Therefore, the production of polysilicon is particularly important for the application of solar energy technology. At present, the modified Siemens method is still the mainstream process for producing polysilicon, accounting for about 97% of the market. In order to ensure product performance, the content of various impurities brought from the raw materials must be strictly controlled during the production process of this process. Among them, the most difficult non-metallic impurity to remove is PCl3.
[0003] PCl3 will seriously affect the performance of solar-grade polysilicon products. In order to ensure product quality, companies generally require that the content of PCl3 in trichlorosilane must be less than 30ppb during the production of solar-grade polysilicon. To this end, necessary separation technology must be adopted. Among the many PCl3 removal technologies, the adsorption method has aroused widespread research interest due to its advantages such as simple operation and low energy consumption. Qian Hao and others from Tianjin University systematically studied the removal effect of common adsorbents on ppm-level PCl3. The results showed that acidic alumina has a great advantage in adsorbing PCl3, indicating that it is an adsorbent that can potentially remove PCl3. However, the main problem with alumina adsorbents is that when the PCl3 concentration is as low as ppb level, alumina has weak adsorption capacity, slow adsorption rate, low adsorption capacity, and cannot effectively remove PCl3. Therefore, it is necessary to develop an adsorbent that can remove PCl3 to the ppb level. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an acetic acid modified alumina coated titanium dioxide adsorbent and a preparation method and application thereof. The present invention uses a titanium source and an aluminum source as raw materials, urea as a precipitant, and obtains an acetic acid modified alumina coated titanium dioxide flower ball-shaped adsorbent by a hydrothermal co-precipitation method, high-temperature calcination and acetic acid impregnation. The interaction between the acetic acid modified alumina coated titanium dioxide adsorbent provided by the present invention and PCl3 can efficiently remove trace amounts of PCl3, and the adsorbent can be recycled and reused multiple times after regeneration, and has good practical value.
[0005] The invention provides an acetic acid modified alumina coated titanium dioxide adsorbent. The adsorbent is in a flower ball shape and comprises a titanium dioxide ball and a sheet-like acetic acid modified alumina embedded on the surface of the titanium dioxide ball.
[0006] Furthermore, the adsorbent comprises mesoporous and macroporous structures, wherein the mesopores account for 95-99%, the average pore size is 10-12 nm, and the specific surface area is 115-183 m 2 / g, pore volume is 0.4~0.6cm 3 / g.
[0007] The present invention also provides a method for preparing the acetic acid modified alumina coated titanium dioxide adsorbent according to the above-mentioned method, firstly, a titanium source, an aluminum source and a precipitant are added into water, a hydrothermal co-precipitation method is used to obtain a precursor, and then the precursor is calcined and modified by acetic acid impregnation to obtain the acetic acid modified alumina coated titanium dioxide adsorbent.
[0008] Furthermore, the titanium source is titanium sulfate; the aluminum source is aluminum nitrate; and the precipitant is urea.
[0009] Furthermore, the mass ratio of the titanium source to the aluminum source is 1:(2.5-3.5); the amount of the precipitant is 1-1.5 times the total mass of the titanium source and the aluminum source; and the amount of water is 45-55 times the total mass of the titanium source, the aluminum source and the precipitant.
[0010] Furthermore, the reaction temperature of the hydrothermal coprecipitation method is 170-190° C., the time is 6-8 hours, and after the reaction is completed, the steps of filtering, washing and drying are also included; the calcination temperature is 500-550° C., the time is 2-2.5 hours, and after the calcination is completed, a cooling step is also included; the acetic acid impregnation modification adopts an acetic acid solution with a concentration of 1.5-1.8 mol / L, the mass volume ratio of the calcined precursor to the acetic acid is 1g: (15-25) mL, and the impregnation is carried out at 22-26° C. for 20-24 hours.
[0011] The present invention also provides an application of the above-mentioned acetic acid-modified alumina-coated titanium dioxide adsorbent in the removal of PCl3.
[0012] Furthermore, the initial concentration of the PCl3 is 10 to 500 ppb; the removal is carried out at 25 to 45°C for 10 to 180 min, and the amount of the adsorbent used is 0.05 g to 0.30 g / 20 mL.
[0013] Furthermore, after the acetic acid-modified alumina-coated titanium dioxide adsorbent adsorbs and removes PCl3, it is calcined and regenerated under an inert atmosphere.
[0014] Furthermore, the calcination temperature is 50-70° C. and the calcination time is 1-1.5 h.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The present invention uses a hydrothermal coprecipitation and room temperature impregnation method to prepare an acetic acid modified alumina coated titanium dioxide adsorbent, which can efficiently remove trace PCl3 by using its interaction with PCl3, and the adsorbent can be repeatedly recycled and reused after desorption, thereby reducing the consumption of the adsorbent and saving costs. The present invention provides a new method for removing trace PCl3.
[0017] The acetic acid modified alumina coated titanium dioxide adsorbent provided by the present invention is an electrophilic adsorbent, which can be combined with electron-rich PCl3, thereby achieving the removal of trace PCl3. In the process of preparing the acetic acid modified alumina coated titanium dioxide adsorbent, the present invention adds titanium sulfate. Both sulfate and titanium ions show strong electron-withdrawing properties. Adding them to alumina can effectively increase its electrophilic point. At the same time, acetic acid is used to impregnate and modify it, which can not only further increase its electrophilic groups, but also increase its specific surface area. Titanium sulfate is used as the titanium source, and titanium dioxide is preferentially generated during the preparation of the adsorbent. The flaky alumina generated subsequently is evenly embedded in the surface of the titanium dioxide spheres, stacked to form a spherical morphology. After being modified by acetic acid, its flower-ball morphology is clearer, and the adsorbent is mainly a mesoporous structure. The prepared acetic acid modified alumina coated titanium dioxide flower-ball shaped adsorbent has a specific surface area of 115 to 183 m 2 / g, pore volume is 0.4~0.6cm 3 / g, and the average pore size is 10-12nm.
[0018] After alumina is coated on the surface of titanium dioxide and impregnated with acetic acid, the surface area is increased, so that its physical adsorption capacity is enhanced; secondly, after acetic acid modification, the carboxyl content on the surface of the adsorbent is greatly increased, which provides more adsorption sites for PCl3; finally, Cl in PCl3 can also interact with Al in Al2O3 and Ti in TiO2 through relatively strong charge transfer, and P in PCl3 can also adsorb with carbonyl O in acetic acid through charge transfer. Thereby achieving the purpose of efficient removal of PCl3. The adsorbent provided by the present invention can remove PCl3 to less than 10ppb, which is better than the commercial resin in the prior art. It avoids the problems of poor stability, high replacement frequency and difficulty in regenerating the adsorbent in the prior art, and it can be regenerated by heating regeneration method, which is simple and efficient. In addition, the adsorbent of the present invention uses inorganic materials during preparation, which greatly reduces the introduction of impurities, so that no new trace impurities are introduced during the application process, and the preparation method is simple, easy to operate, and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 In the figure, (a) is a SEM image of the alumina-coated titanium dioxide adsorbent ([Al2O3]3[TiO2]1) prepared in step (1) of Example 1; (b) is a SEM image of the acetic acid-modified alumina-coated titanium dioxide adsorbent (HAc-[Al2O3]3[TiO2]1) prepared in step (2) of Example 1.
[0021] Figure 2 XRD patterns of [Al2O3]3[TiO2]1 prepared in step (1) of Example 1, HAc-[Al2O3]3[TiO2]1 prepared in step (2), and HAc-[Al2O3]3[TiO2]1 regenerated after adsorbing PCl3 once.
[0022] Figure 3 The infrared spectra of [Al2O3]3[TiO2]1 prepared in step (1) of Example 1, HAc-[Al2O3]3[TiO2]1 prepared in step (2), and HAc-[Al2O3]3[TiO2]1 regenerated after adsorbing PCl3 once.
[0023] Figure 4 This is a graph showing the regeneration stability verification results of the acetic acid modified alumina coated titanium dioxide adsorbent prepared in Example 1.
[0024] Figure 5 This is a graph showing the removal efficiency of trace PCl3 by acetic acid-modified alumina-coated titanium dioxide flower ball adsorbent, commercial activated carbon, 13X molecular sieve, silica, alumina and commercial resin.
[0025] Figure 6 In the figure, (a) to (i) are SEM images of the products prepared in step (1) of Comparative Examples 3 to 4, Example 1, and Comparative Examples 5 to 10, respectively. DETAILED DESCRIPTION
[0026] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0027] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] In the following embodiments, normal temperature refers to 22-26° C., which will not be described again.
[0032] Example 1
[0033] The preparation of acetic acid modified alumina coated titanium dioxide adsorbent is as follows:
[0034] (1) Weigh 0.24g of titanium sulfate and 0.72g of aluminum nitrate nonahydrate, add 1.15g of urea, place in 50mL of ultrapure water, stir and mix evenly, transfer to a 100mL high-pressure hydrothermal autoclave and react at 180°C for 6h. After natural cooling, wash the synthesized product with ultrapure water and dry at 100°C for 6h; then calcine in a muffle furnace at 500°C for 2h to obtain an alumina-coated titanium dioxide adsorbent, which is recorded as [Al2O3]3[TiO2]1.
[0035] (2) Then, 1 g of [Al2O3]3[TiO2]1 was added to 20 mL of 1.67 M acetic acid solution and immersed in a constant temperature shaker (25°C, 200 r / min) for 24 h. After the immersion, the adsorbent was filtered out and washed with ultrapure water until the pH value of the washing solution no longer changed. The acetic acid-modified [Al2O3]3[TiO2]1 was dried in an oven at 60°C for 8 h to obtain an acetic acid-modified alumina-coated titanium dioxide adsorbent, which was recorded as HAc-[Al2O3]3[TiO2]1.
[0036] Figure 1 In the figure, (a) is a SEM image of the alumina-coated titanium dioxide adsorbent prepared in step (1) of Example 1; (b) is a SEM image of the acetic acid-modified alumina-coated titanium dioxide adsorbent prepared in step (2).
[0037] from Figure 1 It can be seen that at a scale of 1 micron, the flower-ball-like morphology of the alumina-coated titanium dioxide adsorbent modified by acetic acid is displayed, and the pattern becomes more fluffy. It not only has a very beautiful morphology, but also has a large specific surface area, which fully displays its active sites and is conducive to the adsorption of PCl3. Figure 1 Comparison between Figure (a) and Figure (b) shows that the alumina-coated titanium dioxide flower ball-shaped adsorbent is modified by acetic acid, and the modified alumina-coated titanium dioxide flower ball-shaped adsorbent becomes more fluffy and close to flower flocs. According to the measurement, the specific surface area of the acetic acid-modified alumina-coated titanium dioxide adsorbent is 167.47 m 2 / g, pore volume is 0.47cm 3 / g, the average pore size is 11nm, mesopores account for 99%, and the rest are macropores.
[0038] Effect verification
[0039] 1. Verify the removal efficiency of trace PCl3 by the acetic acid-modified alumina-coated titanium dioxide adsorbent prepared in Example 1, the specific steps are as follows:
[0040] 20 mL of chloroform solution, 200 ppb PCl3 and 0.20 g of the above-mentioned acetic acid-modified alumina-coated titanium dioxide adsorbent were respectively added to a sealed polypropylene conical flask, and adsorption was carried out at 25°C for 120 min. After the adsorption, the remaining PCl3 impurity content in the solution was detected by ICP-MS, and the removal rate of trace PCl3 impurities was calculated.
[0041] Among them, the removal rate formula of trace PCl3 impurities is:
[0042]
[0043] Where, R is the removal rate (%); C0 is the concentration of PCl3 in the initial solution (μg / L); Ce It is the concentration of PCl3 remaining in the solution after adsorption reaches saturation (μg / L).
[0044] After detection and analysis, the removal rate of PCl3 by HAc-[Al2O3]3[TiO2]1 prepared in Example 1 was 95.1%.
[0045] 2. Verification of regeneration stability of acetic acid modified alumina coated titanium dioxide adsorbent
[0046] According to the method of effect verification 1 above, when HAc-[Al2O3]3[TiO2]1 adsorbs PCl3 to saturation (adsorption for 120 minutes), the adsorbent is placed under nitrogen protection and calcined at 60°C for 1 hour to regenerate the adsorbent to obtain regenerated HAc-[Al2O3]3[TiO2]1.
[0047] Figure 2 The [Al2O3]3[TiO2]1 prepared in step (1) of Example 1, the HAc-[Al2O3]3[TiO2]1 prepared in step (2), and the HAc-[Al2O3]3[TiO2]1 ( Figure 2 The XRD spectrum of the adsorbent (labeled as "HAc-[Al2O3]3[TiO2]1 after regeneration") shows that the composition of the adsorbent did not change significantly before and after surface modification with acetic acid, and it was mainly composed of alumina and titanium dioxide. The diffraction peaks corresponding to the diffraction angles of 18.50°, 37.28°, 46.28°, and 67.03° are alumina, and the standard card number is PDF#13-0373. The diffraction peaks corresponding to the diffraction angles of 25.28°, 36.37°, 48.05°, 55.06°, 62.69°, 70.31°, and 75.03° are titanium dioxide, and the standard card number is PDF#21-1272.
[0048] Figure 3 The infrared spectra of [Al2O3]3[TiO2]1 prepared in step (1) of Example 1, HAc-[Al2O3]3[TiO2]1 prepared in step (2), and HAc-[Al2O3]3[TiO2]1 regenerated after adsorption of PCl3. It can be seen from the figure that 3698.1cm in the spectrum of [Al2O3]3[TiO2]1 -1 is the vibration peak of bound water in titanium dioxide, 3435.9 cm -1 is the stretching vibration of -OH on the surface of aluminum oxide, 572.5 cm -1 After modification by acetic acid, the peaks at 2924.9, 2854.2, 1468.4 and 1421.4 cm -1Four new characteristic peaks appeared nearby, which were -CH, -OH, -C=O and -OH groups of acetic acid. In addition, the infrared spectrum did not change significantly after adsorption, indicating that the adsorbent had good stability.
[0049] The adsorption and removal effect of regenerated HAc-[Al2O3]3[TiO2]1 on PCl3 was verified. Using the same method as mentioned above, after detection and analysis, the final removal rate of PCl3 by the adsorbent was 94.2% after secondary recycling.
[0050] Five consecutive adsorption-regeneration experiments were conducted on HAc-[Al2O3]3[TiO2]1. After detection and analysis, the removal rates of PCl3 by the adsorbent for five consecutive times were 95.1%, 94.2%, 93.7%, 93.3%, and 92.8%, respectively. Figure 4 As shown in the figure, it can be seen that the acetic acid modified alumina coated titanium dioxide adsorbent prepared in this example has relatively stable adsorption performance and good regeneration performance.
[0051] 3. Effect of adsorption temperature on the adsorption and removal of trace PCl3 by acetic acid modified alumina coated titania adsorbent
[0052] The same method as in the above-mentioned effect verification 1 was used to detect the removal rate of PCl3 by HAc-[Al2O3]3[TiO2]1 prepared in Example 1 at different temperatures. It was found that when the adsorption temperatures were 35°C and 45°C, after 120 minutes, the removal rates of PCl3 by HAc-[Al2O3]3[TiO2]1 prepared in Example 1 were 85.4% and 82.5%, respectively.
[0053] 4. Effect of adsorption time on the adsorption and removal of trace PCl3 by acetic acid modified alumina coated titania adsorbent
[0054] The same method as in the above-mentioned effect verification 1 was used to detect the removal rate of PCl3 by HAc-[Al2O3]3[TiO2]1 prepared in Example 1 at different times. It was found that when the adsorption time was 30 min, 60 min, and 180 min, the removal rates of PCl3 by HAc-[Al2O3]3[TiO2]1 prepared in Example 1 were 77.1%, 75.8%, and 95.3%, respectively.
[0055] 5. Effect of initial PCl3 concentration on the adsorption and removal of PCl3 by acetic acid-modified alumina-coated titania adsorbent
[0056] The same method as in the above-mentioned effect verification 1 was used to detect the removal rate of PCl3 by HAc-[Al2O3]3[TiO2]1 prepared in Example 1 at different initial PCl3 concentrations. It was found that when the initial PCl3 concentrations were adjusted to 10ppb, 50ppb, 100ppb, 150ppb and 300ppb, respectively, the removal rates of PCl3 by HAc-[Al2O3]3[TiO2]1 prepared in Example 1 were 5.2%, 19.3%, 65.84%, 82.0% and 81.7%, respectively.
[0057] 6. Effect of adsorbent dosage on the adsorption and removal of PCl3 by acetic acid modified alumina coated titania adsorbent
[0058] The same method as in the above-mentioned effect verification 1 was used to detect the removal rate of PCl3 by HAc-[Al2O3]3[TiO2]1 prepared in Example 1 at different dosages. It was found that when the initial dosage of HAc-[Al2O3]3[TiO2]1 was adjusted to 0.05g, 0.10g and 0.15g, respectively, the removal rates of PCl3 were 67.5%, 80.6% and 90.5%, respectively.
[0059] The present invention explores the optimal conditions for the adsorption of PCl3 by acetic acid modified alumina coated titanium dioxide flower ball shaped adsorbent. It can be seen from the above verification that with the increase of adsorption temperature, the removal rate of PCl3 by acetic acid modified alumina coated titanium dioxide flower ball shaped adsorbent decreases. Therefore, the adsorption should be carried out at a lower temperature to ensure the efficient removal of PCl3 by the acetic acid modified alumina coated titanium dioxide flower ball shaped adsorbent; the adsorption time of acetic acid modified alumina coated titanium dioxide flower ball shaped adsorbent for PCl3 is 120min, and the adsorption is close to equilibrium, and rapid adsorption mainly occurs in the first 40min; the adsorption results of acetic acid modified alumina coated titanium dioxide flower ball shaped adsorbent for different initial concentrations of PCl3 show that acetic acid The saturated adsorption capacity of acid-modified alumina-coated titanium dioxide flower-ball-shaped adsorbent for PCl3 is approximately linearly related to the initial concentration of PCl3, which indicates that acetic acid-modified alumina-coated titanium dioxide flower-ball-shaped adsorbent not only has a high adsorption effect on ppb-level PCl3, but also has excellent adsorption performance for higher concentrations of PCl3; the optimal dosage of acetic acid-modified alumina-coated titanium dioxide flower-ball-shaped adsorbent is 0.2g. Increasing the dosage of adsorbent within a certain range can effectively improve the removal rate, but after exceeding the optimal dosage, further increasing the dosage will not significantly improve the effect, but will increase the cost.
[0060] Example 2
[0061] The preparation of acetic acid modified alumina coated titanium dioxide adsorbent is as follows:
[0062] (1) Weigh 0.24 g of titanium sulfate and 0.94 g of aluminum nitrate nonahydrate, add 1.18 g of urea, place in 129 mL of ultrapure water, stir and mix evenly, transfer to a 200 mL high pressure hydrothermal autoclave and react at 190 ° C for 7 h. After natural cooling, wash the synthesized product with ultrapure water and dry at 100 ° C for 6 h; then calcine in a muffle furnace at 550 ° C for 2 h to obtain an alumina-coated titanium dioxide adsorbent, which is recorded as [Al2O3]3[TiO2]1.
[0063] (2) Then, 1 g of [Al2O3]3[TiO2]1 was added to 25 mL of 1.5 M acetic acid solution and immersed in a constant temperature shaker (22°C, 200 r / min) for 24 h. After the immersion, the adsorbent was filtered out and washed with ultrapure water until the pH value of the washing solution no longer changed. The acetic acid-modified [Al2O3]3[TiO2]1 was dried in an oven at 60°C for 8 h to obtain an acetic acid-modified alumina-coated titanium dioxide adsorbent, which was recorded as HAc-[Al2O3]3[TiO2]1.
[0064] The specific surface area of the acetic acid modified alumina coated titanium dioxide adsorbent prepared in this example is 155.4 m 2 / g, pore volume is 0.5cm 3 / g, the average pore size is 11nm, mesopores account for 98%, and the rest are macropores.
[0065] Example 3
[0066] The preparation of acetic acid modified alumina coated titanium dioxide adsorbent is as follows:
[0067] (1) Weigh 0.24 g of titanium sulfate and 1.31 g of aluminum nitrate nonahydrate, add 2.32 g of urea, place in 175 mL of ultrapure water, stir and mix evenly, transfer to a 300 mL high pressure hydrothermal autoclave and react at 170 ° C for 8 h. After natural cooling, wash the synthesized product with ultrapure water and dry it at 100 ° C for 6 h; then calcine it in a muffle furnace at 520 ° C for 2.5 h to obtain an alumina-coated titanium dioxide adsorbent, which is recorded as [Al2O3]3[TiO2]1.
[0068] (2) Then, 1 g of [Al2O3]3[TiO2]1 was added to 15 mL of 1.8 M acetic acid solution and immersed in a constant temperature shaker (26°C, 200 r / min) for 20 h. After the immersion, the adsorbent was filtered out and washed with ultrapure water until the pH value of the washing solution no longer changed. The acetic acid-modified [Al2O3]3[TiO2]1 was dried in an oven at 60°C for 8 h to obtain an acetic acid-modified alumina-coated titanium dioxide adsorbent, which was recorded as HAc-[Al2O3]3[TiO2]1.
[0069] The specific surface area of the acetic acid modified alumina coated titanium dioxide adsorbent prepared in this example is 132.6 m 2 / g, pore volume is 0.4cm 3 / g, the average pore size is 10nm, mesopores account for 96%, and the rest are macropores.
[0070] The various properties of the acetic acid modified alumina coated titanium dioxide adsorbent prepared in Examples 2 to 3 were verified using the above-mentioned effect verification methods 1 to 5. The results obtained were equivalent to the effects of the acetic acid modified alumina coated titanium dioxide adsorbent prepared in Example 1.
[0071] Comparative Example 1
[0072] 0.2 g of commercial activated carbon, 13X molecular sieve, silica, γ-Al2O3 (alumina) and commercial resin were added to 20 mL of 200 ppb PCl3 solution respectively, adsorbed at 25°C until saturation, and their removal efficiency for trace PCl3 was tested.
[0073] The results are as follows Figure 5 As shown in the figure, the removal efficiencies of trace PCl3 by commercial activated carbon, 13X molecular sieve, silica, alumina and commercial resin are 43.6%, 59.1%, 66.0%, 67.4% and 69.4%, respectively. Figure 5 It can be seen that common adsorbents have a certain removal effect on PCl3, but their removal efficiency is significantly lower than that of the acetic acid modified alumina coated titanium dioxide adsorbent prepared by the present invention. It can be seen that the adsorbent prepared by the present invention has the performance of efficiently removing trace amounts of PCl3 and has a good prospect for development and utilization.
[0074] Comparative Example 2
[0075] 20 mL of chloroform solution, 200 ppb PCl3 and 0.20 g of [Al2O3]3[TiO2]1 prepared in step (1) of Example 1 were added to a sealed polypropylene conical flask respectively, and adsorption was carried out at 25°C for 120 min. After the adsorption, the remaining PCl3 impurity content in the solution was detected by ICP-MS. According to the calculation method in Effect Verification 1, the removal rate of trace PCl3 by [Al2O3]3[TiO2]1 was calculated to be 90.4%.
[0076] The regeneration stability of [Al2O3]3[TiO2]1 prepared in step (1) of Example 1 was verified according to the method in Effect Verification 2. The removal rates of PCl3 for five consecutive times were 90.4%, 88.7%, 87.6%, 87.3% and 87.2% respectively.
[0077] It can be seen from this that the acetic acid impregnation modification can further improve the removal rate of the adsorbent for trace PCl3 and its regeneration stability.
[0078] Comparative Examples 3 to 6
[0079] The same as Example 1, except that the "react at 180°C for 6 hours" in step (1) is modified to "react at 180°C for 1 hour", "react at 180°C for 3 hours", "react at 180°C for 12 hours" and "react at 180°C for 24 hours", that is, the hydrothermal time is modified to 1 hour, 3 hours, 12 hours and 24 hours, respectively.
[0080] Comparative Examples 7 to 8
[0081] Same as Example 1, except that the "react at 180°C for 6 h" in step (1) is changed to "react at 140°C for 6 h" and "react at 220°C for 6 h", that is, the hydrothermal temperature is changed to 140°C and 220°C, respectively.
[0082] Comparative Examples 9 to 10
[0083] The same as Example 1, except that the "calcination in a muffle furnace at 500°C for 2h" in step (1) is modified to "calcination in a muffle furnace at 700°C for 2h" and "calcination in a muffle furnace at 900°C for 2h", that is, the calcination temperatures are modified to 700°C and 900°C, respectively.
[0084] Figure 6 (a) to (i) are SEM images of the products prepared in step (1) of Comparative Examples 3 to 4, Example 1, and Comparative Examples 5 to 10, respectively. Figure 6 It can be seen that when the hydrothermal time is 1 h, only smooth TiO2 microspheres are observed, i.e. Figure 6 Figure (a); When the hydrothermal time is 3h, flower-shaped alumina begins to be observed, i.e. Figure 6 (b) Figure, but the growth of the flower ball alumina is not sufficient. However, too long hydrothermal time will also lead to changes in the shape of the flower ball alumina, such as Figure 6 In the middle (d) figure, when the hydrothermal time exceeds 12h, the adsorbent will be highly aggregated to form rod-like particles. Figure 6 Figure (e). The adsorbent yields at different hydrothermal times are shown in Table 1. The adsorbent yield increases first and then decreases with the extension of the hydrothermal time. In addition, at too high (≥220°C) and too low (≤140°C) hydrothermal temperatures, no alumina-coated titanium dioxide adsorbent can be observed, such as Figure 6 (f) (g) Figure; Too high calcination temperature (≥700℃) may even destroy the morphology and structure of the adsorbent, such as Figure 6Figures (h) and (i). It is precisely because of the above reasons that the adsorbent prepared under these conditions after being modified with acetic acid has a poorer adsorption effect on PCl3 than the adsorbent [Al2O3]3[TiO2]1 prepared under the optimal conditions (i.e., aluminum-titanium mass ratio of 3:1, hydrothermal time of 6h, hydrothermal temperature of 180℃, calcination temperature of 500℃) after being modified with acetic acid (as shown in Table 2, the data in the table are the results obtained by testing according to the method of effect verification 1).
[0085] Table 1 Effect of hydrothermal time on adsorbent yield
[0086]
[0087] Table 2 Adsorption effect of adsorbents prepared under different conditions on PCl3 after modification with acetic acid
[0088]
[0089] In summary, the interaction between the acetic acid-modified alumina-coated titanium dioxide flower ball-shaped adsorbent provided by the present invention and PCl3 can efficiently remove trace amounts of PCl3, and the adsorbent can be reused for multiple cycles after regeneration, which has good practical value.
[0090] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. An acetic acid modified alumina coated titanium dioxide adsorbent, characterized in that: The adsorbent is in the shape of a flower ball, comprising a titanium dioxide ball and a sheet-shaped acetic acid-modified aluminum oxide embedded on the surface of the titanium dioxide ball.
2. The acetic acid modified alumina coated titanium dioxide adsorbent according to claim 1, characterized in that: The adsorbent comprises mesoporous and macroporous structures, wherein the mesopores account for 95-99%, the average pore size is 10-12 nm, and the specific surface area is 115-183 m 2 / g, pore volume is 0.4~0.6cm 3 / g.
3. A method for preparing the acetic acid modified alumina coated titanium dioxide adsorbent according to claim 1 or 2, characterized in that: Firstly, a titanium source, an aluminum source and a precipitant are added into water, and a precursor is obtained by a hydrothermal coprecipitation method. Then, the precursor is calcined and modified by acetic acid impregnation to obtain the acetic acid-modified alumina-coated titanium dioxide adsorbent.
4. The method for preparing the acetic acid modified alumina coated titanium dioxide adsorbent according to claim 3, characterized in that: The titanium source is titanium sulfate; the aluminum source is aluminum nitrate; and the precipitant is urea.
5. The method for preparing the acetic acid modified alumina coated titanium dioxide adsorbent according to claim 3, characterized in that: The mass ratio of the titanium source to the aluminum source is 1:(2.5-3.5); the amount of the precipitant is 1-1.5 times the total mass of the titanium source and the aluminum source; and the amount of water is 45-55 times the total mass of the titanium source, the aluminum source and the precipitant.
6. The method for preparing the acetic acid modified alumina coated titanium dioxide adsorbent according to claim 3, characterized in that: The reaction temperature of the hydrothermal coprecipitation method is 170-190°C, the time is 6-8h, and after the reaction is completed, the steps of filtering, washing and drying are also included; the calcination temperature is 500-550°C, the time is 2-2.5h, and after the calcination is completed, a cooling step is also included; the acetic acid impregnation modification adopts an acetic acid solution with a concentration of 1.5-1.8 mol / L, the mass volume ratio of the calcined precursor to acetic acid is 1g: (15-25) mL, and the impregnation is carried out at 22-26°C for 20-24h.
7. Use of the acetic acid modified alumina coated titanium dioxide adsorbent according to claim 1 or 2 in PCl3 removal.
8. The use according to claim 7, characterized in that: The initial concentration of the PCl3 is 10-500 ppb; the removal is carried out at 25-45°C for 10-180 min, and the amount of the adsorbent used is 0.05 g-0.30 g / 20 mL.
9. The use according to claim 8, characterized in that: After the acetic acid-modified alumina-coated titanium dioxide adsorbent adsorbs and removes PCl3, it is calcined and regenerated under an inert atmosphere.
10. The use according to claim 9, characterized in that: The calcination temperature is 50-70° C. and the calcination time is 1-1.5 hours.
